2020
DOI: 10.4193/rhin19.274
|View full text |Cite
|
Sign up to set email alerts
|

Role of physical exercise type in olfactory deterioration in ageing

Abstract: BACKGROUND: Although ageing and neurodegenerative diseases, including Alzheimer disease, have been associated with olfaction impairment, studies exploring how to ameliorate this impairment are limited. The aim of the present study was to determine the effect of various types of physical exercise on olfaction decline in ageing. METHODOLOGY: 99 healthy community-dwelling participants (85 women; mean (SD) age, 62.5 (5.7) years) were included. All the participants were required to complete the tests consisting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…In humans, exercise improved inspiratory flow through the nose, but this did not result in improved olfactory detection (Marioni et al 2010). A 10-year longitudinal study and a separate 1-year study in aged humans revealed that exercise decreased the risk of developing an olfactory impairment (Schubert et al 2013;Zhang et al 2020). Results from other studies investigating the effect of exercise specifically on olfactory neurons are scarce and mixed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, exercise improved inspiratory flow through the nose, but this did not result in improved olfactory detection (Marioni et al 2010). A 10-year longitudinal study and a separate 1-year study in aged humans revealed that exercise decreased the risk of developing an olfactory impairment (Schubert et al 2013;Zhang et al 2020). Results from other studies investigating the effect of exercise specifically on olfactory neurons are scarce and mixed.…”
Section: Discussionmentioning
confidence: 99%
“…2013; Zhang et al . 2020). Results from other studies investigating the effect of exercise specifically on olfactory neurons are scarce and mixed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also found that different types of sports lead to different effects ( Baches et al, 2018 ), that is, not all types of exercise improve people’s physical or mental health. For example, one study indicated that dance, tai chi, and running significantly improved olfactory function in people, whereas walking did not have the same effect ( Zhang et al, 2020 ). The results of the difference in the two types of exercise examined in the present study may be because dancing requires more cognition than stationary cycling, and brain regions involved in cognition overlap with those involved in emotional regulation, including the PFC.…”
Section: Discussionmentioning
confidence: 99%
“…Weak handgrip strength is indicative of decline in upper extremity strength with high predictive value for adverse outcomes 18 , 19 . Accordingly, physical activity that improves muscle strength might help to prevent olfactory decline 20 . Identifying factors that can exacerbate or mitigate olfactory dysfunction, including comorbidities or lifestyle, could be crucial in establishing public awareness campaigns on related harmful effects 41 .…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the literature review, there is a growing body of literature that recognizes weak handgrip strength as predictive value for adverse outcomes 18 , 19 . Therefore, one might speculate that physical activity and improvements in muscle strength might help to prevent olfactory decline 20 . Based on the above, our hypothesis is that sufficient levels of muscle strength in adulthood and old age could be associated with lower sensory deterioration of smell over the years.…”
Section: Introductionmentioning
confidence: 99%